Bauran Pemasaran Ritel Berbasis Pesantren: Analisis Anomali Spasial terhadap Keputusan Pembelian - Unun Musarofah; Nur Ichan (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
This study aims to analyze the empirical influence of the marketing mix comprising product, price, location, and promotion on consumer purchasing decisions at BMart Tegalrejo, an Islamic boarding school-based (pesantren) community retail enterprise. Utilizing a quantitative causal approach, data were gathered via structured questionnaires distributed to 100 consumers selected through an accidental sampling technique, aligning with a non-probability sampling design. The data were validated through classical assumption tests and estimated using multiple linear regression. The empirical results demonstrate that product, price, and promotion partially exert a positive and statistically significant effect on consumer purchasing decisions. Price emerges as the most dominant predictor of consumer behavior in this religious community with a substantial coefficient (β = 0.7177; p < 0.05). Conversely, a compelling and novel finding reveals that location has no significant partial effect on purchasing decisions (p = 0.0890 > 0.05). This spatial anomaly challenges conventional retail gravity theories, demonstrating that geographic or physical constraints are entirely overridden by strong spiritual motivations, loyalty, and social norms embedded within the boarding school's captive market. Simultaneously, the marketing mix elements exhibit high robust explanatory power, collectively explaining 80.05% of the variance in consumer choices (Adjusted R² = 0.8005). These insights suggest that BMart managers should prioritize price fairness, product Shariah compliance, and community-centric promotions over costly spatial expansions while offering a novel marketing framework for Islamic micro-economies.